Successful Triple Valve Surgery in an Undernourished Patient: What to Prepare? - Dian Paramita Kartikasari; Esti Hindariati (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACT Valvular heart disease accountsfor 10% to 20% of all cardiac surgical procedures in the United States. The decision to intervene, as well as the type of intervention for a patient with severe valvular heart disease, should be based on an individual risk-benefit analysis. Once a patient is considered a candidate for cardiac surgery, a comprehensive patient evaluation of medical conditions and comorbidities helps improve operative outcomes and minimize the mortality rate. Patients with severe valvular heart disease with chronic heart failure at times, progressing to malnutrition. Patients undergoing cardiac surgery experience a systemic inflammatory response, which contributes to acute organ injury leading to a higher incidence of comorbidities and worse malnutrition. Therefore, preoperative risk and nutritional assessment are critical in performing safe cardiac surgical procedures. We report a case of a malnourished 17-year-old man with multiple valvular heart disease with optimal preparation, including good nutritional status leading to good outcome of complex cardiac surgery even in the high risk patients. Keywords : valvular heart disease, malnutrition, perioperative assessmentCorrespondence : dr.dianparamita@yahoo.com